Improving Students' Cognitive Learning Achievement in History Learning Through the Cooperative Script Model and Infographic Media in Class X IPS 1 MA Negeri 2 Surakarta - Siti Nurjanah; Sriyanto Sriyanto (UM Purwokerto Press, 2025)
The purpose of this study is to improve students' cognitive learning achievement in history learning through the cooperative script model and infographic media. This study uses a quantitative approach with an experimental method in one class. Data collection was carried out through pretest, posttest and observation. The data analysis technique used SPSS with the Paired Sample T Test technique. Based on the results of the study, the Sig. (2-tailed) value was obtained at 0.000 <0.05, so we can conclude that there is a significant difference between learning outcomes in the Pre-test and Post-test data.